Length-Weight Relationship Analysis and Condition Factor of Fish in Lake Chini: Reason For Population Depletion - Kutty, Ahmad Abas; Baharuddin, Haslawati; Agustar, Hani Kartini; Eziwar Dyari, Herryawan Ryadi; W Muhamad, Wan Maisarah; Abas, Nur Amelia (Malaysian Applied Biology, 2026)
Lake Chini’s fish are important as a pool of ichthyodiversity of the Pahang River drainage and a natural food resource for the native community nearby. However, the fish population was shrinking after a disastrous flood in 1995, and it is still a puzzle as to the cause of the decline of the fish population. This study aims to estimate the fish growth pattern using the length–weight relationship (LWR) analysis and condition factor. The study evaluated b and K values from the LWR analysis equation. B value is the slope of the LWR, which indicates the growth pattern (e.g., isometric or allometric), while K value refers to the condition factor, which shows the overall health of fish. Fishes were sampled using a gill net and identified to species level, and water quality was analysed using standard methods. Lake Chini was found to have a good to moderate water quality status, ranging from category A to category C according to the Malaysian Lake Water Quality Standard (NLWQS). The Carlson trophic index has classified the lake water bodies into an early eutrophic status. The LWR analysis on four selected fish species showed the mean b value ranged between 2.07 and 4.02, implying negative isometric growth for most of the species and isometric and positive growth for one species, which is K. cryptopterus and C.rapasson respectively. Fish length significantly influenced weight, with coefficients of determination ranging from 69% to 98%. The K value ranged from 1.00 to 1.08, indicating that the fish is in a moderate condition of well-being. This study indicates that water quality, food sources, and habitat are not the significant factors that cause fish depletion in Lake Chini.